Does sustainable consumption matter? Consumer grocery shopping behaviour and the pandemic - Ing Grace Phang; Bamini KPD Balakrishnan; Hiram Ting (Emerald Publishing Limited, 2021)
Purpose – The COVID-19 pandemic took the world by surprise in early 2020. The preventive measures imposed by many countries limited human movement, causing uncertainty and disrupting consumption patterns and consumer decision-making. This study aims to explore consumers’ panic buying (PB) and compulsive buying (CB) as outcomes of the intolerance of uncertainty (IU). The moderating role of sustainable consumption behaviours (SCBs) (e.g. quality of life [QOL], concern for future generation and concern for environmental well-being) were also tested to raise awareness of responsible and mindful consumption amongst the society and business stakeholders. Design/methodology/approach – To empirically examine the grocery shopping behaviours of Malaysian consumers during COVID-19, a total of 286 valid grocery consumer survey responses based on a purposive sampling were collected and analysed during the movement control order period between March and July 2020. Findings – The findings confirmed the statistically significant impact of IU on both PB and CB and the impact of PB on CB behaviour. Amongst the three SCBs tested, only QOL significantly moderated the relationship between the IU and PB. Originality/value – To the best of the authors’ knowledge, this is the first study to construct a framework of consumers’ PB and CB during the pandemic, building upon the stimulus-organism-response model and the concepts of IU and SCB. This study further serves as the pioneering study on the moderating role of SCB in consumer behaviour research in the pandemic context, whereby consumers’ QOL significantly moderates the relationship between their IU and PB. This study has also drawn specific implications for grocery retailers and government agencies for retail and policy planning to promote positive social transformation in consumer buying behaviours during a pandemic or crisis.